Beetroot (Beta vulgaris L.) Extract Gives Superior Effect than Beetroot Juice on Increasing HDL and Decreasing LDL and IL-6 in Dyslipidemic Rats Model - Riri, Miftahul Jannah; Harioputro, Dhani Redhono; Wardhani, Lusi Oka (The Indonesian Biomedical Journal, 2024)
BACKGROUND: Dyslipidemia derives from disturbances in lipid metabolism as an interaction between genetic and environmental factors, characterized by increased levels of cholesterol, triglycerides, low-density lipoprotein (LDL) and decreased levels of high-density lipoprotein (HDL). Continuous dyslipidemia will increase the risk of atherosclerosis. In dyslipidemia, macrophages release inflammatory cytokines such as interleukin (IL)-1, IL-6, IL-12, IL-15, IL-18, and then induce T-cell infiltration formed atherosclerotic plaques. Beet (Beta vulgaris L.) which contains active compounds and antioxidant, such as flavonoids and betacyanin, has the ability to reduce dyslipidemia. This study evaluated effect of beetroot juice and beetroot extract on dyslipidemic rat models by evaluating the level of HDL, LDL and IL-6.METHODS: Fourty-two male Sprague Dawley rats were divided into seven groups. Rats were fed either with standard food or high fat diet (HFD) for 28 days, then different interventions using either single combination of simvastatin, beetroot juice, or beetroot extract were given alongside the standard food or HFD diet for another 28 days. LDL and HDL were measured pre- and post-intervention, while IL-6 was measured only post-treatment.RESULTS: Daily administration of a single beetroot juice or beetroot extract or in combination with simvastatin reduced LDL significantly compared to pre-intervention. The interventions also increased HDL significantly and lower IL-6 concentrations compared to group that received no intervention.CONCLUSION: Administration of beetroot juice and beetroot extract can lower LDL, increase HDL, and decrease IL-6 either alone or in combination treatment with simvastatin, it is indicated beetroot have a potential benefit for prevention and therapeutic in dyslipidemia.KEYWORDS: beetroot juice, beetroot extract, LDL, HDL, IL-6